Data Infrastructure as Court Architecture - Albrecht, Kat (Science and Technology Law Review, 2025)
Whether courts like it or not, digital legal data has become an important part of both litigation and justice administration. Constitutionally protected as public records, court data and court-adjacent data must be made transparent and accessible to the general public. However, alongside considerations of how to make court data accessible externally, so must we also consider how court data is situated internally within courts. Conceptualizing data infrastructure as court architecture reframes the importance of court data to better align with its current utility in courts, while privileging the very real structural issues that courts must contend with to ensure the continued health of data systems. This Article considers the usefulness of data in the current terrain of law and justice, evaluates the ecosystem of data products currently at play in all levels of courts, and offers concrete pathways to data infrastructure development through Open Knowledge Networks.